Characteristics of trauma mortality in the Northern Territory, Australia - Kathleen M. McDermott; Matt B. Brearley; Steven M. Hudson; Linda Ward; David J. Read (BMC, 2017)
Abstract Background While factors including remoteness, alcohol consumption, age and Indigenous ethnicity are well-documented associations of trauma mortality, less is known of trauma seasonality. This is particularly relevant to Australia's Northern Territory, with its tropical regions experiencing a climate of wet (hot and humid) and dry (warm) seasons annually. The aim of this study was to therefore, examine the characteristics of trauma mortality in the Top End, Northern Territory, Australia. Methods A retrospective review of the National Coroners Information System (NCIS) database from 1 January 2003 to 31 December 2007 analysed four-h﻿undred and sixt﻿een﻿ traumatic deaths where the trauma event and death occurred within the Top End of the Northern Territory. Results The annual traumatic death rate for the Top End was 58.7 per 100 000, with variance between regions (accessible 38.1; remote 119.1 per 100000, respectively). Overall alcohol was involved in 56.5% of cases. The three most frequent mechanisms of death were suicide, transport related and assault, accounting for 81.5% of deaths. These respective mechanisms of death demonstrated seasonal influence, with transport related deaths 2.5 times more likely to occur in the dry than the wet season (p < 0.001), while assault related deaths were 3.3 times more likely to occur during the wet season (p = 0.005), and suicide was 1.6 times more likely to occur during the wet season (p = 0.022). Transport related deaths were 2.2 times more likely in remote and very remote settings than in accessible or moderately accessible regions (p < 0.003), whereas death by suicide was less likely to occur in remote and very remote regions than in accessible or moderately accessible areas (p = 0.012). Conclusion Excessively high rates of traumatic death in the Top End of the Northern Territory were evident, with contrasting seasonal﻿ and regional profiles. Based upon the data of this investigation, existing programmes to minimise trauma in the Northern Territory ought to be evaluated for seasonal and regional specificity.